IMPROVEMENT OF MOTHER'S BREAST MILK PRODUCTION THROUGH PAPAYA FRUIT DESSERT - Sripatima -; Endah Wahyutri; Ega Ersya Urnia (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Breast milk (ASI) is the primary source of nutrition for infants as it can fulfill all their needs. However, the current rate of exclusive breastfeeding is still low. In Kutai Kartanegara Regency, the coverage of exclusive breastfeeding is only 47.5%. One of the reasons is insufficient breast milk production. Various efforts have been made to enhance breast milk production, such as providing papaya fruit dessert, as it contains lactagogue compounds that have the potential to stimulate hormones like oxytocin and prolactin. Compounds such as alkaloids, polyphenols, steroids, flavonoids, and other substances are believed to be most effective in increasing and facilitating breast milk production. To analyze the influence of papaya fruit dessert consumption on the enhancement of breast milk production among postpartum mothers in the working area of Sungai Merdeka Community Health Center in 2023. This study employs a quasi-experimental design with a "Pretest-Posttest, Control Group Design." The population includes all postpartum mothers who have given birth normally in the working area of Sungai Merdeka Community Health Center, with an average of 30 deliveries per month. The sample size was determined using the minimal sample size formula by Lemeshow, resulting in 26 participants. The measurement tools consist of observation sheets and a real bubee electric breast pump. Data analysis involves an independent t-test. There is an influence of papaya fruit dessert consumption on the enhancement of breast milk production among postpartum mothers in the working area of Sungai Merdeka Community Health Center, with a p-value of 0.000. The breast milk production in the group provided with papaya fruit dessert was significantly higher, with a difference of 39,231 ml compared to the group without papaya fruit dessert. The presence of compounds like alkaloids, polyphenols, steroids, and flavonoids in papaya fruit can enhance breast milk production.